TNFSF13 upregulation confers chemotherapeutic resistance via triggering autophagy initiation in triple-negative breast cancer - Lin, Hui-Yu; Kuei, Chia-Hao; Lee, Hsun-Hua; Lin, Che-Hsuan; Chen, Yen-Lin; Chen, Chi-Long; Lin, Yuan-Feng (Journal of molecular medicine (Berlin, Germany), 2020)
Since chemotherapy is a main strategy to treat triple-negative breast cancer (TNBC) patients currently, identifying a biomarker to predict chemotherapeutic responses is urgently needed for patients to avoid suffering through unnecessary chemotherapeutic treatments. Here, we found that the endogenous expression of TNFSF13 in a panel of TNBC cell lines highly correlates with paclitaxel (PTX) and doxorubicin IC 50 concentrations. Whereas knocking down TNFSF13 enhances PTX effectiveness in PTX-insensitive MDA-MB231 cells, recombinant TNFSF13 (recTNFSF13) desensitizes PTX-sensitive HCC1806 cells to PTX treatment. Moreover, Kaplan-Meier analysis revealed that higher TNFSF13 mRNA expression significantly predicts an increased risk for cancer recurrence in estrogen receptor (ER)-negative breast cancer patients receiving an anthracycline-based treatment. Accordingly, immunohistochemistry experiments indicated that higher levels of TNFSF13 protein are detected in TNBC patients who do not respond to an anthracycline-based treatment. The in silico analysis and Western blotting demonstrated that TNFSF13 expression inversely associates with the activity of the Akt-mTOR pathway, which acts as a negative regulator of autophagy activity. Significantly, the pharmaceutical inhibition of autophagy activity restores the therapeutic effectiveness of PTX in TNFSF13-treated HCC1806 cells. These findings suggest that TNFSF13 can serve as a predictive biomarker for TNBC patients, who can use it to decide whether to receive chemotherapy. Key messages TNFSF13 upregulation correlates with a poor response to chemotherapy in TNBCs. TNFSF13 promotes autophagy initiation in chemotherapeutic resistant TNBCs. Therapeutic targeting of autophagy initiation overcomes the TNFSF13-related chemoresistance. TNFSF13 could be a predictive biomarker for TNBC patients receiving chemotherapy.